2020
DOI: 10.1021/acschembio.0c00104
|View full text |Cite
|
Sign up to set email alerts
|

Obtusaquinone: A Cysteine-Modifying Compound That Targets Keap1 for Degradation

Abstract: We have previously identified the natural product obtusaquinone (OBT) as a potent antineoplastic agent with promising in vivo activity in glioblastoma and breast cancer through the activation of oxidative stress; however, the molecular properties of this compound remained elusive. We used a multidisciplinary approach comprising medicinal chemistry, quantitative mass spectrometry-based proteomics, functional studies in cancer cells, and pharmacokinetic analysis, as well as mouse xenograft models to develop and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The standard initial approach is maximal safe surgical resection, followed by radio-and chemotherapy, and treatment options in the recurrent setting are less well defined, with no established standard of care [2]. Some molecules have recently been identified that can influence the development of glioblastoma and the course of the disease, such as obtusaquinone [3], coronarin D [4], betulinic acid [5], icaritin [6], and others. As early as 1995 Magrassi et al [7] had demonstrated that activated 1α,25(OH) 2 vitamin D 3 or calcitriol (1α,25(OH) 2 VD3) was capable of inducing a significant (>50%) reduction in growth of glioblastoma cells at dosages over 5 µM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard initial approach is maximal safe surgical resection, followed by radio-and chemotherapy, and treatment options in the recurrent setting are less well defined, with no established standard of care [2]. Some molecules have recently been identified that can influence the development of glioblastoma and the course of the disease, such as obtusaquinone [3], coronarin D [4], betulinic acid [5], icaritin [6], and others. As early as 1995 Magrassi et al [7] had demonstrated that activated 1α,25(OH) 2 vitamin D 3 or calcitriol (1α,25(OH) 2 VD3) was capable of inducing a significant (>50%) reduction in growth of glioblastoma cells at dosages over 5 µM.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1995 Magrassi et al [7] had demonstrated that activated 1α,25(OH) 2 vitamin D 3 or calcitriol (1α,25(OH) 2 VD3) was capable of inducing a significant (>50%) reduction in growth of glioblastoma cells at dosages over 5 µM. Classically, the inactive form of vitamin D3 or cholecalciferol is first hydroxylated in carbon 25 in the liver to form 25(OH) vitamin D 3 or calcidiol and then it is hydroxylated in carbon 1 in the kidney to form 1α,25(OH) 2 VD3. Interestingly, glioblastoma was able to metabolize cholecalciferol to calcidiol [8].…”
Section: Introductionmentioning
confidence: 99%
“…OBT could bind to cysteine residues of Keap1 with specific affinity and lead to Keap1 somatic degradation and activation of Nrf2 downstream expression factors. The ability of OBT was also confirmed to penetrate the protective barrier of the brain and work in the brain (Badr et al, 2020). The possible mechanism of action of OBT and its ability to penetrate the BBB greatly enhances its feasibility in studies related to PD prevention and treatment.…”
Section: Modification Of Keap1 Cysteine Residues By Nrf2 Covalent Act...mentioning
confidence: 85%
“…Multiple compounds have been tested for clinical efficacy, however, none of the proposed approaches has demonstrated success in clinical trials. A natural product obtusaquinone (OBT) has been shown to downregulate the Nrf2 pathway through binding to Keap1 cysteine residues and promoting its proteasomal degradation [ 74 ]. Malignant GBM phenotype is dependent on metabolic alterations which also show an association with the Nrf2 activity.…”
Section: Significance Of Nrf2 In Clinical Practice and Gbm Treatment ...mentioning
confidence: 99%